METODE PENILAIAN PERTUMBUHAN BALITA TERKINI (TEMU ILMIAH NASIONAL PERSAGI, 2023)
It is very important to determine and monitor the growth of toddlers regularly and properly to find out early on nutritional problems in an area. One of the techniques in assessing children's growth is the anthropometric method. There are four important things in assessing growth, namely first, being obedient in following weighing or measuring procedures; secondly, using the right tools in an effort to comply with these procedures; third, accurate in recording; and fourth, right in interpretation. The methods that have been suggested so far are weighing, measuring height, and calculating the Body Mass Index (BMI), which is a combination of the child's weight and length or height. The anthropometric index most frequently used to detect a child's health condition every month and to describe the current nutritional status is Weight for Age (BB/U). The second index which is also important in describing past nutritional status is Body Length or Height for Age (BB/U), and to see both how the growth of weight and length or height of children according to their age is the Body Mass Index for Age (BMI). /u). Weighing and measurement results must be recorded and plotted for later interpretation. For children who have problems with their growth, they must receive special attention so that the next weighing and measurement leads to normal growth.